Potensi Sorgum sebagai Bahan Pangan Fungsional - Suarni Suarni (Puslitbang Tanaman Pangan, 2012)
The advantage of sorghum as food is that it has rich in functional food components. Various antioxidants, trace elements especially iron, dietary fiber, oligosaccharides, -glucans, including non-starch polysaccharide carbohydrate components (NSP) is contained in the sorghum grain, making potential as a source of functional food. The uniqueness of sorghum is that tannin and phytic acid each has characteristics of negative and positive impact on health. The antioxidant property of tannins is higher than vitamin E and C, and the antioxidant anthocyanin in sorghum is more stable. Functional food elements that contain bioactive components give physiological effects including strengthening the bodys immune system, regulate the rhythm of physical conditions, slow down aging, and help prevent degenerative disease. Utilization of sorghum in diversified processed products requires proper processing technology so the functional food components remain in the ready to consume food product. Thus, sorghum is not an inferior food, but actually a superior ones. Increasing the societys knowledge and awareness on the maintaining of health is an important step for choosing a diet. Sorghum-based product not only contains functional food components but also is suitable to people with gluten allergies. The availability of good local and improved varieties of sorghum needs to be utilized more intensively on food processing.